More Than Meets the Eye in Bacterial Cellulose: Biosynthesis, Bioprocessing, and Applications in Advanced Fiber Composites - Lee,K-Y; Buldum,G; Mantalaris,A; Bismarck,A (Macromolecular Bioscience, 2014)
Bacterial cellulose (BC) nanofibers are one of the stiffest organic materials produced by nature. It consists of pure cellulose without the impurities that are commonly found in plant-based cellulose. This review discusses the metabolic pathways of cellulose-producing bacteria and the genetic pathways of Acetobacter xylinum. The fermentative production of BC and the bioprocess parameters for the cultivation of bacteria are also discussed. The influence of the composition of the culture medium, pH, temperature, and oxygen content on the morphology and yield of BC are reviewed. In addition, the progress made to date on the genetic modification of bacteria to increase the yield of BC and the large-scale production of BC using various bioreactors, namely static and agitated cultures, stirred tank, airlift, aerosol, rotary, and membrane reactors, is reviewed. The challenges in commercial scale production of BC are thoroughly discussed and the efficiency of various bioreactors is compared. In terms of the application of BC, particular emphasis is placed on the utilization of BC in advanced fiber composites to manufacture the next generation truly green, sustainable and renewable hierarchical composites.